Epigenetics in neonatal necrotizing enterocolitis: current understanding and the potential involvement of m6A modification - Chen, Yixian; Chen, Yujun (Frontiers in Pediatrics, 2025)
Necrotizing enterocolitis (NEC) exhibits high incidence, surgical intervention rates, and mortality among preterm infants, profoundly impacting survivor's long-term quality of life. Consequently, the etiology and pathogenesis of this disease remain incompletely elucidated. Emerging evidence underscores the intricate connection between epigenetics and NEC. DNA methylation, histone modifications, and non-coding RNAs regulate disease development through targeted modification of transcriptional regulation and translational control in NEC-associated genes, thereby driving pathological progression. Notably, N6-methyladenosine (m6A) modification, the most prevalent form of RNA epigenetic regulation, exerts critical functions in intestinal inflammation, microbial homeostasis, and injury repair, suggesting its potential involvement in NEC development. In this review, we will summarize the current mechanistic understanding of NEC, emphasizing its interplay with epigenetics (DNA methylation, histone modifications, and non-coding RNAs). we also explore the emerging role of m6A RNA modification in gut pathophysiology, proposing its potential role in NEC.